The effect organic solvent extract of Datura metel leaves on some biological aspects of Hyalomma schulzei (olenev) (Acari:Ixodidae) - Wathah, Esraa F.; Annon, Mohamad R. (Al-Qadisiyah Journal of Pure Science, 2017)
The current studay include the investigation of impact organic solvent extract(Ethyl alcohol, Ethyl acetate, Hexan ) of Datura metel leaves on immature and adult stage of the ticks Hyalomma schulzei under laboratory conditions. Biological activity of extracts was determined using different concentrations (10,30,50,70)%. The results showed the followings: Mortality eggs and larvae after exposure to different concetraction to three Solvent reahed 90% the mortarty of non-feedeing nymphs reached 90%, 77.7%, 68.85% and feedeing nymphs reached %83.85 , 72.78 % , 66.14% respectively at the Concentration of 70 mgwhile mortility rate of adult stage non-feedeing males90% , 61.22% , 59% and feedeing77.7% , 57% , 51.14% while non-feedeing females 72.29%, 53.15% , 46.92% . and the feedeingfemales 63.93%, 51.84%, 40.7at concentration 70 mgafter exposur to previously extract on respectively. The result indicated that Ethyalcohol. extracts were more effective than Ethyle acetate and Hexan.